2014
DOI: 10.1371/journal.pone.0104829
|View full text |Cite
|
Sign up to set email alerts
|

Gene Knockout and Overexpression Analysis Revealed the Role of N-Acetylmuramidase in Autolysis of Lactobacillus delbrueckii subsp. bulgaricus Ljj-6

Abstract: Autolysis of lactic acid bacteria (LAB) plays a vital role in dairy processing. During cheese making, autolysis of LAB affects cheese flavor development through release of intracellular enzymes and restricts the proliferation of cells in yogurt fermentation and probiotics production. In order to explore the mechanism of autolysis, the gene for the autolytic enzymes of L. bulgaricus, N-acetylmuramidase (mur), was cloned and sequenced (GenBank accession number: KF157911). Mur gene overexpression and gene knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…S2A and B). Previous research has demonstrated that Lactobacillus species can undergo autolysis in the late stationary phase, especially in response to carbon starvation (25,26). BHI medium only contains 0.2% (wt/vol) glucose, so we tested whether glucose limitation induced autolysis under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…S2A and B). Previous research has demonstrated that Lactobacillus species can undergo autolysis in the late stationary phase, especially in response to carbon starvation (25,26). BHI medium only contains 0.2% (wt/vol) glucose, so we tested whether glucose limitation induced autolysis under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that some lactic acid bacteria can undergo enzymatic cleavage of cell wall peptidoglycans by peptidoglycan hydrolases present in the bacterial cells and that the autolysis depends on factors, such as carbon source, temperature, osmotic concentration, and pH [56]. It has also been demonstrated that N-acetylmuramidase has a critical function in Lactobacillus bulgaricus autolysis [57] as one of the major degraders of the cell wall. In our experiment, the percentage of live L. plantarum cells was significantly lower after 48 h than at the beginning or after 24 h. Moreover, significant differences in L. plantarum morphology were observed.…”
Section: Acrylamide Impact On Lab Viabilitymentioning
confidence: 99%
“…To delete the fbpA gene from the genome of W. cibaria isolate LW1, a homologous recombination procedure was performed employing the suicide vector pUC19 (Pang, Cui, Liu, Zhang, & Lv, ). DNA fragments for 630 bp upstream and 670 bp downstream of fbpA gene were amplified using the specific primer pairs fbpAUp‐F/fbpAUp‐R and fbpADown‐F/fbpADown‐R, respectively, (Table ).and cloned into pUC19 with digestion and ligation.…”
Section: Methodsmentioning
confidence: 99%